CCDC114, DNAI2 and TOP2A involves in the effects of tibolone treatment on postmenopausal endometrium. - Lv, Yanhua; Liu, Yanqing; Wang, Yueqiang; Kong, Fanrong; Pang, Qiuxiang; Hu, Guirong (BMC Women's Health, 2021)
Background: This study aimed to explore the molecular mechanisms of tibolone treatment in postmenopausal women.Methods: The gene set enrichment profile, GSE12446, which includes 9 human endometrial samples from postmenopausal women treated with tibolone (tibolone group) and 9 control samples (control group), was downloaded from GEO database for analysis. Differentially expressed genes (DEGs) in tibolone vs. control groups were identified and then used for function and pathway enrichment analysis. Protein-protein interaction (PPI) network and module analyses were also performed. Finally, drug-target interaction was predicted for genes in modules, and then were validated in Pubmed.Results: A total of 238 up-regulated DEGs and 72 down-regulated DEGs were identified. These DEGs were mainly enriched in various biological processed and pathways, such as cilium movement (e.g., CCDC114 and DNAI2), calcium ion homeostasis, regulation of hormone levels and complement/coagulation cascades. PPI network contained 368 interactions and 166 genes, of which IGF1, DNALI1, CCDC114, TOP2A, DNAH5 and DNAI2 were the hue genes. A total of 96 drug-gene interactions were obtained, including 94 drugs and eight genes. TOP2A and HTR2B were found to be targets of 28 drugs and 38 drugs, respectively. Among the 94 obtained drugs, only 12 drugs were reported in studies, of which 7 drugs (e.g., epirubicin) were found to target TOP2A.Conclusions: CCDC114 and DNAI2 might play important roles in tibolone-treated postmenopausal women via cilium movement function. TOP2A might be a crucial target of tibolone in endometrium of postmenopausal women.